WEIGHTED SPACES - Moya Lázaro, Nancy (2011)
In this paper, we present an analytical study of a class of weights, we formulate some properties and some estimates of these. From finimos corresponding Sobolev spaces with weights, try to establish some relations between Sobolev spaces with weight and weightless. We built Sobolev inclusions weighing between Sobolev spaces with weight.